2011
DOI: 10.1038/jid.2010.371
|View full text |Cite
|
Sign up to set email alerts
|

The Role of R-Spondin2 in Keratinocyte Proliferation and Epidermal Thickening in Keloid Scarring

Abstract: Keloids are found only in humans and the underlying biochemical mechanisms of their pathogenesis remain unknown. R-spondins (Rspos) are a relatively new group of secreted proteins known to be Wnt/β-catenin signaling agonists, but their role in keloids has yet to be elucidated. We investigated the expression levels of R-spondin2 (Rspo2) in cell lysates and conditioned media of monocultures and co-cultures of fibroblasts and keratinocytes derived from keloids and normal skin. In this study we found increased pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 40 publications
3
33
0
1
Order By: Relevance
“…WNT genes are required for blastema formation (Kawakami et al, 2006; Stoick-Cooper et al, 2007). In addition, several studies have linked WNT signaling to tissue repair and wound healing, including in skin and bone (Chen et al, 2007; Chua et al, 2011; Fathke et al, 2006; Lim et al, 2013; Whyte et al, 2013). It is tempting to speculate that the observed requirement for WNT signaling during the induction of the pluripotent state represents a cell culture equivalent to these in vivo regenerative processes.…”
Section: Discussionmentioning
confidence: 99%
“…WNT genes are required for blastema formation (Kawakami et al, 2006; Stoick-Cooper et al, 2007). In addition, several studies have linked WNT signaling to tissue repair and wound healing, including in skin and bone (Chen et al, 2007; Chua et al, 2011; Fathke et al, 2006; Lim et al, 2013; Whyte et al, 2013). It is tempting to speculate that the observed requirement for WNT signaling during the induction of the pluripotent state represents a cell culture equivalent to these in vivo regenerative processes.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence to show that the canonical Wnt/b-catenin signalling is involved in keloid pathogenesis [4]. Sato first reported that TGF-b induced the upregulation of Wnt/b-catenin signalling in hypertrophic scar and keloid fibroblasts (KFs) [5].…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal expression of RSPO2 or RSPO3 has been identified in 10% of colorectal cancer cases (Wu et al 2014). Moreover, RSPO2 can also induce proliferation of another epithelium, the epidermis during keloid scarring (Chua et al 2011). Rspo3 ablation in mice is lethal at 10 days post coitum (dpc).…”
Section: Rspo a Family Of Genes Regulating Morphogenesis And Maintenmentioning
confidence: 99%